Pengaruh Penyuluhan Kesehatan Tentang Stunting Dengan Media Booklet Dan Audiovisual Terhadap Pengetahuan Pada Mahasiswa Pgsd Semester V Di Universitas Pgri Silampari Kota Lubuklinggau - Milanisti, Anggi Yanda Putri; Darmawansyah, Darmawansyah; Sulastri, Mepi (Utami Publisher, 2025)
Stunting is defined as the percentage of children aged 0 to 59 months who have a height below minus (moderate and severe stunting) and minus three (chronic stunting) as measured using child growth standards issued by WHO, which according to WHO standards related to stunting prevalence should be less than 20% (UNICEF 2020). Lubuklinggau City has a prevalence rate of 20.8% and a decrease in 2022 of 11.7%. The purpose of this study was to determine the extent of student knowledge, especially UNPARI students in the PGSD Study Program regarding stunting. This type of research uses a quantitative approach. The research method used is a pre-experimental design with a one group pretest and posttest design. The population in this study were all 5th semester PGSD students for the period 2023 to 2024, namely 264 people. The sampling technique used in this study was cross sectional. Data analysis in this study used the dependent T test while the statistical test results using non-parametric Wilcoxon obtained a p value of 0.001 < α 0.05. The results of the univariate test before the study were 10 people knew about stunting or 14.1%. And after the research was done it became 93.0%. Bivariate analysis results state that there is an effect of health counseling using booklet and audiovisual media, namely with a P value of 0.001 less than the significance value <0,05. It is hoped taht student will be able to seek information about helath throught the use of booklet and audivisual media and calrify understanding to students so that they can contribute to the prevention of stunting.